Movimentos sociais e práxis educativa na construção da Universidade Estadual de Goiás - Alves, Maria de Lourdes (2019)
This thesis is linked to the research line "Education, Work, and Social Movements" of the Postgraduation Program in Education of the Federal University of Goiás (UFG). It seeks to investigate, in a bibliographical and documentary character, such as newspapers, e-mails, discussion forums, pamphlets, photographs and laws, the action of the social movements of teachers, students and servants of the State University of Goiás in the process of construction of higher education institution, as well as the educational praxis developed in the dynamics of the social movements of UEG. The movements delimited for the purposes of the research developed were the UEG/2006 Defense Forum and the Mobiliza UEG/2013. The analysis was carried out under a praxiological perspective and its main objective is to understand the educational praxis present in the social movement and the educational possibilities that create and recreate subjects capable of constituting a new habitus and this, in turn, capable of promoting the emergence of new agents in a given field. The understanding of the object of research is anchored in a significant bibliographical research, especially in: Abreu, (2017); Bourdieu, (1989, 1998, 2001, 2009, 2014); Carvalho, (2013, 2017); Gohn, (2011, 2012, 2013) Oliveira e Pessoa, (2013); Person, (1999,2004); Scherer-Warren, (2006, 2014). The research developed for this thesis shows that the social movements analyzed significantly influenced the institutional development of the UEG and enabled an educational praxis to create new practices and new subjects.